Matrix-type Power Electronic Transformer for PMSG-based Wind Power Generation System - WANG Hui; SU Mei (Kongzhi Yu Xinxi Jishu)
In order to achieve voltage scaling and galvanic isolation between the input side and output side of wind energy conversion system, a matrix-type power electronic transformer (PET) was proposed for PMSG-based wind energy conversion system, which has the advantages of sinusoidal input and output currents, requiring no energy storage elements, high power density, high reliability, high efficiency and low cost. After introducing the topology and operating principles, a control scheme was developed for the presented PET. With the developed control scheme, rectification stage of the PET is used to realize power factor correction at the input side, and isolated high frequency DC-DC converter is equipped to achieve voltage scaling and galvanic isolation, while the inversion stage is used for tracking the maximum power point of wind power and regulating the output power factor. Therefore, it is an attractive solution for high power PMSG-based direct-drive wind power generation system. Simulation results verified the correctness and feasibility of the method.